The Impact of Online Game Addiction and Transformations of Emotional Intelligence and Intellectual Intelligence in Middle Adolescents - Kaimudin, Eggiz Chintya; Diyanah Syolihan Rinjani Putri; Priambodo, Galih (International Journal of Public Health Excellence (IJPHE), 2024)
Adolescence is a critical stage towards adulthood, marked by physical, cognitive and emotional changes. Rapid growth, identity conflicts, and attraction to peers influence development. Online game addiction is increasingly widespread, which can disrupt emotional and intellectual intelligence. Negative impacts include mental health disorders, decreased academic achievement, and disturbances in social interactions and self-regulation. The aim of this research is to determine the relationship between online game addiction and changes in emotional intelligence and intellectual intelligence in middle stage adolescents at SMKN 1 Banyudono. This research is a quantitative study with a cross-sectional design. This research used a total sampling technique with a sample size of 51 respondents. This research instrument uses the Game Addiction Scale (GAS) questionnaire which consists of 21 statements, an emotional intelligence questionnaire with 40 statements and an intellectual intelligence questionnaire with 6 statements. Data were analyzed using Spearman's rank test and regression test. The results of bivariate analysis using the Spearman's rank test obtained a p-value of 0.000 (p-value < 0.005) indicating that there is a significant relationship between online game addiction and changes in emotional intelligence, and a p-value of 0.000 (p-value < 0.005) indicates that there is significant relationship between online game addiction and changes in intellectual intelligence. And the results of multivariate analysis using the regression test obtained a p-value of 0.000 (p-value <0.005). So, it can be concluded that there is a significant relationship between online game addiction and changes in emotional intelligence and intellectual intelligence in middle stage adolescents at SMKN 1 Banyudono